Protein reviews. Volume 17 - Atassi, M. Zouhair (Springer, 2017)
The aim of the Protein Reviews is to serve as a publication vehicle for review articles that focus on crucial current vigorous aspects of protein structure, function, evolution and genetics. Volume 17 of Protein Reviews is the beginning of a new publication format. The volumes will appear online before they are published in a printed book. Articles will be selected according to their importance to the understanding of biological systems, their relevance to the unravelling of issues associated with health and disease or their impact on scientific or technological advances and developments. The chapters in this volume are authored by experts in the field. They deal with aspects of structure and biological activity of selected proteins. Specific chapters deal with the aggregation of FET proteins (FUS, EWSR1, TAF15) as a pathological change in amyotrophic lateral sclerosis, structural changes fundamental to gating of the cystic fibrosis transmembrane conductance regulator anion channel pore, the dual roles for epithelial splicing regulatory proteins 1 (ESRP1) and 2 (ESRP2) in cancer progression, controlling autolysis during flagella insertion in Gram-negative bacteria, the regulation of skeletal muscle myoblast differentiation and the proliferation by pannexins, hyaluronidase and chondroitinase, factors that control mitotic spindle elongation, how secreted phospholipase A2 type IIA (sPLA2-IIA) activates integrins in an allosteric manner, the simple and unique allosteric machinery of Thermus caldophilus lactate dehydrogenase, and the reduction of chemically stable multibonds: Nitrogenase-like biosynthesis of tetrapyrroles. This volume is intended for research scientists, clinicians, physicians, and graduate students in fields of biochemistry, cell biology, molecular biology microbiology, immunology and genetics.
Includes index.
Keywords: Proteins.; elektronické knihy; electronic books